2016
DOI: 10.1016/j.jmbbm.2015.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical changes in the Achilles tendon due to insertional Achilles tendinopathy

Abstract: Insertional Achilles tendinopathy (IAT) is a painful and debilitating condition that responds poorly to non-surgical interventions. It is thought that this disease may originate from compression of the Achilles tendon due to calcaneal impingement. Thus, compressive mechanical changes associated with IAT may elucidate its etiology and offer clues to guide effective treatment. However, the mechanical properties of tissue have not been characterized. Therefore, the objective of this study was to measure the mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 23 publications
0
21
0
2
Order By: Relevance
“…8 Tendinopathy is also associated with changes in tendon mechanics, with IAT tendons demonstrating increased compressive modulus compared with healthy controls, indicating an intrinsically more rigid tissue. 9 These histological changes in IAT tendon are nearly identical to tendon alterations caused by high levels of transverse compression. [10][11][12] Specifically, in vivo studies indicate that regions of tendon adjacent to bone that experience repeated compression exhibit increased type II collagen and aggrecan content, decreased collagen alignment and increased compressive modulus characteristics generally associated with cartilage.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…8 Tendinopathy is also associated with changes in tendon mechanics, with IAT tendons demonstrating increased compressive modulus compared with healthy controls, indicating an intrinsically more rigid tissue. 9 These histological changes in IAT tendon are nearly identical to tendon alterations caused by high levels of transverse compression. [10][11][12] Specifically, in vivo studies indicate that regions of tendon adjacent to bone that experience repeated compression exhibit increased type II collagen and aggrecan content, decreased collagen alignment and increased compressive modulus characteristics generally associated with cartilage.…”
mentioning
confidence: 71%
“…At the tendon insertion of patients with IAT there are increased cartilage matrix proteins (type II collagen and aggrecan) and rounder tendon cells, which suggest metaplasia to cartilage cells (chondrocytes) . Tendinopathy is also associated with changes in tendon mechanics, with IAT tendons demonstrating increased compressive modulus compared with healthy controls, indicating an intrinsically more rigid tissue . These histological changes in IAT tendon are nearly identical to tendon alterations caused by high levels of transverse compression .…”
mentioning
confidence: 94%
“…Also in humans, it has been shown that static training leads to increased tendon stiffness whereas dynamic training does not 44 . Another study in human tendons has also reported that healthy tendons are softer and more compliant compared to tendons with tendiopathy 45 .…”
Section: Discussionmentioning
confidence: 92%
“…To analyze acquired load-extension (i.e., force-displacement) curves and determine the non-linear mechanical properties of tested tendons, the ramp to failure portion of each mechanical test was fit to a piecewise bilinear function as described previously. 15,16 The slope of the first portion of the bilinear fit was taken to be the toe stiffness of the specimens, a measure of its resistance to deformation at small extensions. The slope of the second portion of the bilinear fit was taken to be the linear stiffness of the specimen, a measure of its resistance to deformation at large extensions.…”
Section: Mechanical Testing On Un-injured Tendonmentioning
confidence: 99%